Entrepreneurship : Pretenses Ind. / Norlizawati Nawi ... [et al.] - Nawi, Norlizawati; Abd.Latiff, Azura; Mohd.Nor, Normazlina; Mohamad Yusoff, Mahani; Mohd.Kamil @ Wahab, Nik Rozlinawati (2002)
The PRETENSES INDUSTRY SDN. BHD Was fully owned by Bumiputera, it is situated in Lot 324, Kg Geting, 16200 Tumpat Kelantan. We run the business that manufactured Bilis sauce (Budu) with a capital RM 27 000.